2022
DOI: 10.1002/aenm.202200708
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Electrochemical Analysis: Worth the Effort to Reveal New Insights into Energy Materials

Abstract: and the effectiveness and durability of the materials applied, researchers always call for reliable and detailed knowledge of the mechanism(s) of both, main and side reactions, and especially for their kinetics. In order to gain the relevant information, a large number of methods have been proposed to characterize battery materials, battery electrodes and their interfaces, and battery cells. But when samples are taken out of the cells and analyzed later, there is a high risk of both, contamination and changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 105 publications
(177 reference statements)
0
9
0
3
Order By: Relevance
“…For example, despite significant advancements in the operando X-ray diffraction (XRD) technique, detecting the surface amorphous structure of materials and designing the operando cell remains a challenging task. [23] Additionally, although operando X-ray absorption spectroscopy (XAS) is sensitive to the local coordination structure and oxidation state of elements in materials, it provides only averaged information of bulk materials and tends to lack specificity in reflecting the information regarding formation or catalytic processes taking place at the surface region, and the limited availability and high cost of beam time have restricted its widespread usage. [21,23] Moreover, in situ transmission elec-tron microscopy (TEM) characterization provides a direct means of observing the structural changes in materials.…”
Section: In Situ and Operando Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, despite significant advancements in the operando X-ray diffraction (XRD) technique, detecting the surface amorphous structure of materials and designing the operando cell remains a challenging task. [23] Additionally, although operando X-ray absorption spectroscopy (XAS) is sensitive to the local coordination structure and oxidation state of elements in materials, it provides only averaged information of bulk materials and tends to lack specificity in reflecting the information regarding formation or catalytic processes taking place at the surface region, and the limited availability and high cost of beam time have restricted its widespread usage. [21,23] Moreover, in situ transmission elec-tron microscopy (TEM) characterization provides a direct means of observing the structural changes in materials.…”
Section: In Situ and Operando Techniquesmentioning
confidence: 99%
“…[23] Additionally, although operando X-ray absorption spectroscopy (XAS) is sensitive to the local coordination structure and oxidation state of elements in materials, it provides only averaged information of bulk materials and tends to lack specificity in reflecting the information regarding formation or catalytic processes taking place at the surface region, and the limited availability and high cost of beam time have restricted its widespread usage. [21,23] Moreover, in situ transmission elec-tron microscopy (TEM) characterization provides a direct means of observing the structural changes in materials. However, it faces challenges in terms of fabricating the in situ cell and potential electron beam damage.…”
Section: In Situ and Operando Techniquesmentioning
confidence: 99%
“…Besides advantages like high temporal and spectral resolutions and sensitivities [3], the weak water signals make Raman spectroscopy an ideal tool for the in situ/in operando investigation of aqueous electrochemical reactions. Several Raman spectroelectrochemical studies have improved the understanding of electroorganic synthesis [7][8][9][10][11], electrocatalysis [12,13], batteries [14], electrode interface behavior [15], and material science [16]. Also, molecule/surface interactions without applied potentials can be examined [17].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the background fluorescence emission arising from these components makes it more challenging to analyze Raman spectroscopic data on these cycled materials due to the spectroscopic overlap of Raman scattering and fluorescence emission. 16 One methodology that can overcome the challenges of Raman/emission signal overlap is Kerr-gated Raman spectroscopy. 17 , 18 It has previously been demonstrated that Kerr-gated Raman spectroscopy can be exploited to effectively remove the fluorescence background on uncycled, cycled, and aged battery and electrolyte materials and reveal the Raman scattering signals.…”
mentioning
confidence: 99%
“…During the electrochemical cycling of Li-ion batteries with conventional Li­[PF 6 ]/carbonate-based electrolytes, fluorescent species are formed by parasitic decomposition reactions, primarily due to the instability of the non-aqueous electrolytes and side reactions that occur at the electrode surface. The increase in the background fluorescence emission arising from these components makes it more challenging to analyze Raman spectroscopic data on these cycled materials due to the spectroscopic overlap of Raman scattering and fluorescence emission . One methodology that can overcome the challenges of Raman/emission signal overlap is Kerr-gated Raman spectroscopy. , It has previously been demonstrated that Kerr-gated Raman spectroscopy can be exploited to effectively remove the fluorescence background on uncycled, cycled, and aged battery and electrolyte materials and reveal the Raman scattering signals .…”
mentioning
confidence: 99%